1993
DOI: 10.1068/p221121
|View full text |Cite
|
Sign up to set email alerts
|

Object and Head Orientation Effects on Symmetry Perception Defined by Shape from Shading

Abstract: A grey disc which exhibits a vertical gradient of shading usually appears convex if lighter above and concave if lighter below. This phenomenon was investigated by Howard et al (1990) who varied both the shading axis relative to gravity and the orientation of the head. Their results indicated that head-centric or retinocentric coordinates determined the depth effect rather than gravitational axes. However, several possible problems with their study were noted, not the least of which was the possible intrusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Although some studies showed a contribution from gravitational coordinates (Nicholls, Smith, Mattingley, & Bradshaw, 2006) most of them showed stronger dependence of perception and aftereffects on retinotopic coordinates (Friederici & Levelt, 1990; Mast, Ganis, Christie, & Kosslyn, 2003; Wenderoth & Hickey, 1993). The face inversion effect also generally follows the retinotopic coordinate system (Lobmaier & Mast, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Although some studies showed a contribution from gravitational coordinates (Nicholls, Smith, Mattingley, & Bradshaw, 2006) most of them showed stronger dependence of perception and aftereffects on retinotopic coordinates (Friederici & Levelt, 1990; Mast, Ganis, Christie, & Kosslyn, 2003; Wenderoth & Hickey, 1993). The face inversion effect also generally follows the retinotopic coordinate system (Lobmaier & Mast, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Research into the cerebral basis of shape from shading has suggested that the estimation of the light source direction depends on a low level mechanism, within early visual areas (Gerardin, Kourtzi, & Mamassian, 2010;Humphrey et al, 1997;Mamassian, Jentzsch, Bacon, & Schweinberger, 2003). Behavioral data have offered some confirming evidence to this idea, for example, demonstrating that the light source is predominantly represented in retinal or head-centric coordinates (Howard, Bergstrom, & Ohmi, 1989;Kleffner & Ramachandran, 1992;Wenderoth & Hickey, 1993) but gravitational influences on shape judgments have also been found (Adams, 2008;Yonas, Kuskowski, & Sternfels, 1979).…”
Section: Introductionmentioning
confidence: 91%
“…The assumption continued to hold until the shading axis was rotated 60°with respect to the median plane of the subject's head. Wenderoth and Hickey (1993), who employed a task in which subjects' reaction times and accuracies in determining symmetry of shaded displays were measured, found a gradual reduction in performance as the orientation ofshading moved from orthogonal to the median plane of the head to parallel.…”
mentioning
confidence: 99%